2020
DOI: 10.1155/2020/5040521
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoring Interventions in COPD Patients: Overview of Systematic Reviews

Abstract: Objective. The role of telemonitoring interventions (TIs) for chronic obstructive pulmonary disease (COPD) has been studied in many systematic reviews (SRs) and meta-analyses (MAs), but robust conclusions have not been reached due to wide variations in scopes, qualities, and outcomes. The aim of this overview was to determine the effectiveness of TIs on COPD patients. Methods. PubMed, EMBASE, Web of Science, and Cochrane Library were searched for all reviews on the topic of TI in treating COPD from inception t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
1
19
0
5
Order By: Relevance
“…Vianello, A., et al contradicts this information, with negative results in quality of life and a RCT with 578 patients intervened by Lilholt PH, et al exposed a non-superior health-related quality of life in a 12-months follow-up [32,33]. Other data suggests it might not have impact in reducing mortality and exacerbation-related outcomes in COPD [35], with others showing reticence regarding the application of these interventions in a generalized way (34), stating that the benefits might come from the fact that patients submitted to clinical trials have more attention and support with the disease than otherwise they would receive. Few reports also established positive results and possibilities for the successful application of telemonitoring interventions: with regard to noninvasive ventilation [38] forced expiratory volume [39], peripheral oxygen saturation [28,29,42] and physical activity [12].…”
Section: Telemonitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Vianello, A., et al contradicts this information, with negative results in quality of life and a RCT with 578 patients intervened by Lilholt PH, et al exposed a non-superior health-related quality of life in a 12-months follow-up [32,33]. Other data suggests it might not have impact in reducing mortality and exacerbation-related outcomes in COPD [35], with others showing reticence regarding the application of these interventions in a generalized way (34), stating that the benefits might come from the fact that patients submitted to clinical trials have more attention and support with the disease than otherwise they would receive. Few reports also established positive results and possibilities for the successful application of telemonitoring interventions: with regard to noninvasive ventilation [38] forced expiratory volume [39], peripheral oxygen saturation [28,29,42] and physical activity [12].…”
Section: Telemonitoringmentioning
confidence: 99%
“…Concerning mortality rates, a recent 12-months RCT by Kessler, R., et al [18] revealed a reduced acute care hospitalization days and mortality rate in severe COPD patients. Nevertheless, four reviews stated that telemonitoring and tele-health programs failed to significantly reduce mortality [24,26,35,41]. In addition to usual care, patients in the intervention group received a set of telehealth care equipment and were monitored by a community-based healthcare team.…”
Section: Exacerbations Of Copd and Mortality Ratesmentioning
confidence: 99%
“…Existen estudios que han demostrado resultados positivos en pacientes enfermedades crónicas progresivas como falla cardiaca (10,11). Enfermedad Pulmonar Obstructiva Crónica (12), hepatopatía crónica(13) así como en pacientes con cáncer (14,15). Esfuerzos anecdóticos recientes están evaluando esta tecnología para comunidades rurales (16).…”
Section: Tipos De Intervención De Telesaludunclassified
“…Healthcare increasingly embraces technologies introduced to ease, reorganize, or streamline a specific task; for instance, measurements and devices in telemonitoring [ 4 , 5 , 6 ]. When appropriate, such technologies constitute powerful tools for self-surveillance, education, and self-reliance [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%